Faktor-Faktor Keterlambatan Proses Pelayanan Klaim Asuransi (BPJS) Di Rumah Sakit Bersalin Annisa Pekanbaru - Nur Maimun; Rahimul Rifqi (Jurnal Kesehatan Komunitas, 2020)
Claims of naontial health insurance is a series of acvies to research and prove that there have been reasonable transactions and ordinary and making payments appropriate at apredetermined me. The purpose of this research was to find out the factors service process claims of health insurance in maternity hospital Pekanbaru subjects. This was a qualitativestudy. There were 3 informants from this research. The data collecon was used observation and interviews. The results of the study indicate that the process of filing a claim is to prepare a claim file which will be verified by an administrative officer who if approved, the claim submission form will be printed, and then the claim can be paid. To standard procedures of these hospital policies was there but from Health of Ministry there has been not yet. Human resources service process insurance claims color according to diagnose Indonesian Code Disease 10 and analysis document completeness. Facilities in-service process claims arenot enough and the documents will be decoding died and every day. And analyze the completeness of documents. As a conclusion, the obstacles that existed during the implementation of the National Health insurance claim service process were notrunning optimally, including delays in the National Health insurance claim service process. For the standard procedures, the insurance claim service process for National Health Insurance is already available, but the role of the Health Ministry does not yet exist. Facilities are still lacking. While the files that are coded every day there are fiy pieces. Human resources need to be increased so that the implementation is optimal. Keywords : Delayed, Service process for Naotinal Health insurance claims, Hospital.